Activated TLR signaling in atherosclerosis among women with lower Framingham risk score: the multi-ethnic study of atherosclerosis. - Chiang-Ching Huang; Kiang Liu; Richard M Pope; Pan Du; Simon Lin; Nalini M Rajamannan; Qi-Quan Huang; Nadereh Jafari; Gregory L Burke; Wendy Post; Karol E Watson; Craig Johnson; et al. (PLoS ONE)
Background Atherosclerosis is the leading cause of cardiovascular disease (CVD). Traditional risk factors can be used to identify individuals at high risk for developing CVD and are generally associated with the extent of atherosclerosis; however, substantial numbers of individuals at low or intermediate risk still develop atherosclerosis. Results A case-control study was performed using microarray gene expression profiling of peripheral blood from 119 healthy women in the Multi-Ethnic Study of Atherosclerosis cohort aged 50 or above. All participants had low (<10%) to intermediate (10% to 20%) predicted Framingham risk; cases (N = 48) had coronary artery calcium (CAC) score >100 and carotid intima-media thickness (IMT) >1.0 mm, whereas controls (N = 71) had CAC<10 and IMT <0.65 mm. We identified two major expression profiles significantly associated with significant atherosclerosis (odds ratio 4.85; P<0.001); among those with Framingham risk score <10%, the odds ratio was 5.30 (P<0.001). Ontology analysis of the gene signature reveals activation of a major innate immune pathway, toll-like receptors and IL-1R signaling, in individuals with significant atherosclerosis. Conclusion Gene expression profiles of peripheral blood may be a useful tool to identify individuals with significant burden of atherosclerosis, even among those with low predicted risk by clinical factors. Furthermore, our data suggest an intimate connection between atherosclerosis and the innate immune system and inflammation via TLR signaling in lower risk individuals.